Flavor changing interaction models and strictly massless neutrinos - Pleitez, V (Iop Publishing Ltd, 2000)
It is well known that experimental data, coming from solar and atmospheric neutrino detectors and also from experiments which look for neutrino oscillations. strongly suggest that neutrinos must have a mass different from zero. However at least the solar and/or the atmospheric neutrino data can be related to new flavor changing interactions beyond the standard model instead to the finite mass of neutrinos. This new physics may induce i) extra effects in neutrino-matter interactions, ii) CP violation in pion and lepton decays and, iii) muonium to antimuonium transition. We give two examples of models in which all those effects arise even with strictly massless neutrinos: the 331 model and multi-Higgs doublet extension of the standard model (mHDM) with flavor changing neutral currents in the charged lepton sector. It means that in this kind of models if neutrino masses were eventually needed, they will be independent of the parameters of the new interactions.